Effect of different drying methods on the amino acids, α-dicarbonyls and volatile compounds of rape bee pollen - Yanxiang Bi; Jiabao Ni; Xiaofeng Xue; Zidan Zhou; Wenli Tian; Valérie Orsat; Sha Yan; Wenjun Peng; Xiaoming Fang (Food Science and Human Wellness)
The significant demand for high quality food has motivated us to adopt appropriate processing methods to improve the food nutritional quality and flavors. In this study, the effects of five drying methods, namely, pulsed vacuum drying (PVD), freeze drying (FD), infrared drying (IRD), hot-air drying (HAD) and sun drying (SD) on free amino acids (FAAs), α-dicarbonyl compounds (α-DCs) and volatile compounds (VOCs) in rape bee pollen (RBP) were determined. The results showed that FD significantly released the essential amino acids (EAAs) compared with fresh samples while SD caused the highest loss. Glucosone was the dominant α-DCs in RBP and the highest loss was observed after PVD. Aldehydes were the dominant volatiles of RBP and SD samples contained more new volatile substances (especially aldehydes) than the other four drying methods. Comprehensively, FD and PVD would be potential methods to effectively reduce the quality deterioration of RBP in the drying process.